Dampak Gawai terhadap Perkembangan Anak Usia Pra Sekolah pada Masa Pandemi Covid-19 - Andra Saferi Wijaya; Nehru Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study explores parents' perceptions of the impact of gadgets on children's development after preschool at PAUD IT Baitul Izzah Bengkulu City. The research method is qualitative with a phenomenological approach. The results of the study found six interrelated themes about the impact of gadgets on children's development. The first theme is meaning for parents about giving gadgets to children; the second theme shows the content opened by children on gadgets. The third theme is the duration of using gadgets for children aged 4-6. years, the fourth theme is control over the use of devices in children, and the fifth theme is the impact of machines on child development. In conclusion, the use of gadgets in children has a positive and negative effect on child development. Keywords: Children, Covid-19, Device, Parents, Pandemic, Development